MENUMBUHKAN MINAT MEMBACA SEBAGAI UPAYA PENINGKATAN MUTU TENAGA PENDIDIK PAUD DI INDONESIA - Surtiawati, Cucu (JIV-Jurnal Ilmiah Visi, 2009)
In this information and knowledge era, people tend to develop their expertise by obtaining information and knowledge as much as and as fast as possible. They will stand behind if they do not follow and adapt the advanced science and technology. Reading is a tool to obtain many kinds of information and reading habit is a precondition to build and develop reading society. However, reading has not become a habit aand reading interest is not high enough for most most of people in Indonesia. Reading skill and reading habit of the teachers of early childhood education are suspected unsatisfactory. This article discusses how to create reading interest and develop reading habit of the teachers of early childhood teachers as a means of improving their quality.